Analisis Swot Pada Perusahaan Manufaktur PT. Astra Honda Motor Dimasa Pandemi Covid – 19 - Zahra Nur Maulidia; Daspar Daspar (Jurnal Ekonomi dan Bisnis Digital, 2025)
The COVID-19 pandemic has impacted various industrial sectors, including the automotive industry in Indonesia. PT Astra Honda Motor (AHM), as the market leader in motorcycles in Indonesia, faces major challenges in maintaining operational stability and business sustainability. This study aims to analyze business strategies using the SWOT (Strengths, Weakness, Opportunities, Threats) analysis method during the pandemic. Data was obtained through literature studies, company annual reports, and other secondary sources. The results of the analysis show that AHM's main strengths lie in its strong brand image, extensive distribution network, and technological support from Honda Japan. However, a glaring weakness is the dependence on the supply of imported components which was disrupted during the pandemic. Opportunities arise from the increasing demand for private vehicles and electric motorcycles, while the biggest threat comes from the decline in consumer purchasing power and restrictions on economic activity. The recommended strategy is to maximize strengths to seize post-pandemic market opportunities and minimize internal weaknesses to reduce the impact of external threats.